"But it's just paracetamol" : caregivers ability to administer over-the-counter painkillers to their children with the information provided - Gibson, Fiona (Department of Public Health and Family Medicine, 2015)
Unintentional overdose of over-the-counter (OTC) medications has become an increasing global public health concern due to the common and frequent use of painkillers among end users, to self-medicate and medicate others, without fully understanding the associated health risks. While many developed countries have started to implement measures in an attempt to reduce access to large quantities and raise awareness of the dangers of misuse of OTC medications, this is not the case in many middle and low income countries. Instead, many individuals are forced to rely on written information while faced with poor health literacy, inadequate information and limited verbal information from health professionals, all of which contribute to the increase in unsafe behaviours leading to overdosing. In South Africa, most unintentional overdoses from OTC painkillers occur in children, which can often be attributed to incorrect dosing from caregivers. With the common practice of re-packaging medications at a distribution level, individuals are often not provided with adequate information about their medication, appropriate for their level of health literacy. This study explored whether caregivers are able to make informed decisions about the correct and safe administration of popular OTC painkillers (specifically paracetamol) to their children, based on information from labels, medication inserts and/or patient information leaflets (PILs).